I have series $\sum_{n=2}^{\infty} \frac{n+1}{n^3-1} $

I think that comparison test would give the easiest solution but i'm not sure how to apply it. I know that i need to find larger sum to prove convergence or smaller to prove divergence, so

$\frac{1}{n} $ would give us larger sum (correct me if i am wrong), and we know that $\sum_{n=0}^{\infty} \frac{1}{n} $ diverges, therefore our series from beginning of question diverges, but wolfram alpha said that $\sum_{n=2}^{\infty} \frac{n+1}{n^3-1} $ by comparison test converges.

Where am i making mistake, and what is the best way to apply comparison test on $\sum_{n=2}^{\infty} \frac{n+1}{n^3-1} $?

  • $\begingroup$ try $\sum_{n=2}^{\infty} \frac{2}{n^2+n+1}$. $\endgroup$
    – Yiyi Rao
    Nov 10, 2016 at 17:48
  • $\begingroup$ If you have $0\le u_n\le v_n$, and $\sum v_n$ is not convergent, then you can't say anything about $\sum u_n$. $\endgroup$ Nov 10, 2016 at 17:52
  • 1
    $\begingroup$ $\frac{n+1}{n^3-1}\sim\frac{1}{n^2}$, so $\sum u_n$ is convergent. $\endgroup$ Nov 10, 2016 at 17:54
  • $\begingroup$ The comparison test says if you're "bigger" than a divergent, then you're divergent, and if you're "smaller" than a convergent, then you're convergent. Remember that for non-negative series, convergence and divergence are basically "size" concepts. $\endgroup$
    – AJY
    Nov 10, 2016 at 17:56
  • 1
    $\begingroup$ @TarsNolan Yes, but a constant factor catches that. If you compare to $\frac{2}{n^2}$, you have $\frac{n+1}{n^3-1} < \frac{2}{n^2}$ for $n \geqslant 2$. If you pick any $c > 1$, you have $\frac{n+1}{n^3-1} < \frac{c}{n^2}$ for all large enough $n$. $\endgroup$ Nov 10, 2016 at 18:26

2 Answers 2


Compare the given series with $\sum_{n=1}^\infty v_n=\sum\dfrac{1}{n^2}$.

If $u_n=\dfrac{n+1}{n^3+1}$ and $v_n=\dfrac{1}{n^2}$

then $\dfrac{u_n}{v_n}=\dfrac{(n^2)( n+1)}{n^3+1}=\dfrac{1+\dfrac{1}{n}}{1+\dfrac{1}{n^3}}\to 1<\infty$ as $n\to \infty$

Since $\sum_{n=1}^\infty \dfrac{1}{n^2}$ converges so does $\sum u_n=\sum\dfrac{n+1}{n^3+1}$


What about exploiting creative telescoping? For any $n\geq 2$ we have $$ 0\leq \frac{n+1}{n^3-1} \leq \frac{1}{n(n-1)}=\frac{1}{n-1}-\frac{1}{n}\tag{1}$$ hence: $$ 0\leq \sum_{n=2}^{N}\frac{n+1}{n^3-1}\leq \sum_{n=2}^{N}\frac{1}{n(n-1)} = 1-\frac{1}{N}<1.\tag{2}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.